2013
DOI: 10.1111/fcre.12032
|View full text |Cite
|
Sign up to set email alerts
|

Iaals' Honoring Families Initiative: Courts and Communities Helping Families in Transition Arising from Separation or Divorce

Abstract: Keypoints It is time for a national dialogue about the feasibility of creating out‐of‐court alternatives for separating and divorcing families. Research indicates that separating parents who provide their children with consistency, emotional support, and low conflict help children successfully adapt in the transition process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 37 publications
2
39
0
Order By: Relevance
“…This is consistent with Kourlis, Taylor, Schepard, and Pruett's (2013) finding in Australia. This is consistent with Kourlis, Taylor, Schepard, and Pruett's (2013) finding in Australia.…”
Section: Lessons Learned From Implementation Partnershipssupporting
confidence: 92%
See 2 more Smart Citations
“…This is consistent with Kourlis, Taylor, Schepard, and Pruett's (2013) finding in Australia. This is consistent with Kourlis, Taylor, Schepard, and Pruett's (2013) finding in Australia.…”
Section: Lessons Learned From Implementation Partnershipssupporting
confidence: 92%
“…54 No. Kourlis, Taylor, Schepard, and Pruett (2013) identified that helping parents through the transition of separation and divorce and supporting unmarried parents requires the skills of multimodal and systemically integrated professionals. According to McLanahan (2004), the shifts associated with the second demographic transition has led to two different trajectories for women with differential implications for children.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a voluminous literature on the benefits of third-party dispute resolution processes like mediation and facilitation (see summary in Kourlis, Taylor, Schepard, & Pruett, 2013), but its effectiveness among unique subpopulations, including unmarried parents in the child support system, has not been extensively evaluated. The limited evidence available, however, suggests that unmarried parents in the child support system also benefit from third-party dispute resolution processes.…”
Section: Mediation and Facilitation By A Neutral Third Partymentioning
confidence: 99%
“…With the proposed exception of de minimis costs associated with the inclusion of a parenting time provision entered as part of a child support order (OCSE, 2014), child support agencies may not obtain FFP for activities pertaining to parenting time. This unfunded congressional aspiration coincides with severe cuts to many state court budgets and the consequent dismantling of existing parenting services for separating and divorcing parents (Kourlis, Taylor, Schepard, & Pruett, 2013) that would otherwise be the natural entities to serve the new, unmarried parents in the child support system. More to the point, while Public Law 113-183, enacted in September 2014, includes a provision (Section 303) that creates the goal of establishing voluntary parenting time arrangements accompanied by strong family violence safeguards in child support orders, it offers no funding or access to FFP.…”
mentioning
confidence: 99%